2014
DOI: 10.1177/0363546514530092
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Subjective, Clinical, and Radiographic Outcome Evaluation of Meniscal Allograft Transplantation in the Knee

Abstract: Despite an increase in joint space narrowing, MAT resulted in significant improvements in pain and functional outcomes over the study period. There was no change in these improvements between the medium- and long-term follow-up period. This study confirms the good and consistent results found in the literature concerning satisfaction, pain resolution, and functional scores at long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
3
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(74 citation statements)
references
References 18 publications
2
64
3
5
Order By: Relevance
“…Using a Wilcoxon signed rank test to compare pre-operative Lysholm scores and Lysholm scores at final follow-up showed that there is a significant difference between these scores ( P  < 0.005). However, it can be noted as shown in Figure 3 that patients who filled in the Lysholm questionnaire report less profit of MAT [5, 9, 11, 14, 17, 21, 23, 29, 40, 45, 46, 54, 57, 61, 62, 64, 66]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a Wilcoxon signed rank test to compare pre-operative Lysholm scores and Lysholm scores at final follow-up showed that there is a significant difference between these scores ( P  < 0.005). However, it can be noted as shown in Figure 3 that patients who filled in the Lysholm questionnaire report less profit of MAT [5, 9, 11, 14, 17, 21, 23, 29, 40, 45, 46, 54, 57, 61, 62, 64, 66]. …”
Section: Resultsmentioning
confidence: 99%
“…Less pain and swelling of the knee joint allow for more of their daily activities. However, pain seems to return over time, as patients who filled in the VAS-chart tend to report more pain (Figure 5) [4, 5, 15, 17, 21, 22, 27, 33–35, 37, 38, 47]. In the analysis of the KOOS-score, 12 papers were included.…”
Section: Resultsmentioning
confidence: 99%
“…Reoperations occur in 35% of patients, with 12% requiring conversion to total knee arthroplasty, based on a study of 49 patients with a mean follow-up of almost 13 years. 134 For others the outcome is more favorable, with significant improvement in pain and function in addition to generally well preserved joint spaces.…”
Section: Replacement Allograftmentioning
confidence: 99%
“…Few large, long-term studies of meniscal allograft transplantation have been performed with the longest follow-up with 7 years, thereby making a modeling approach useful in identifying the optimal treatment over the long term [10,21,22]. Given the large cost discrepancy between the available procedures, a cost-effectiveness analysis is needed to determine whether the cost of meniscal allograft is outweighed by the ability to delay the need for TKA in this patient population.…”
Section: Introductionmentioning
confidence: 99%